Developing systemic solutions for typhus fever eradication in resurgent Poland between 1918 and 1924 - Agnieszka Polak; Anna Zagaja; Maria Cichecka (Polish Pharmaceutical Society, 2023)
Research's subject The research's subject includes fundamental principles and procedures for taking preventive activities against infections. Although such a holistic solution is the domain of contemporary times, the legal solutions introduced during the current Covid pandemic were created on the basis of legislature and solutions first introduced over 100 years ago as a result of the typhus epidemic. The legislators of those times already noticed the necessity to take anti-epidemic, and preventive measures in order to neutralize the sources of infections, and cut down the spread route. The study presents solutions introduced during the typhus epidemic occurring on the Polish territories (Central Europe) in the years between 1918 and 1924. Archival epidemiological data along with taken steps and measures (including the establishment of special state institutions) are presented showing how the epidemic of those times provided the fundament for preventing epidemics on the Polish territory. Research's aim The purpose of the research is to present, in a chronological manner, the formation of systemic solutions for combating the epidemic of typhus, which broke out in the resurgent Polish lands at the end of WWI. Material and method Presented data are based on documents and archival materials, which include registers of typhus patients from general hospitals between 1918 and1924, information from the Central Military Archives, information obtained from historical sources including medical journals of that period, as well as information from the national archives and the Central Statistical Office. These data were analyzed and presented. Results The manuscript presents data on incidence and mortality. It also consists of a step-by-step analysis of introduced preventive measures along with the problems that were caused by their enforcement, including social distrust and resistance. Conclusions Enacted institutions, including the Polish Institute of Hygiene, allowed for greater monitoring of public health. The typhus experience facilitated the development of hospital networks and provided medical care to society. What is more, because of an urgent need to educate medical staff, the training of doctors, nurses, and other medical professionals was launched in 1921 as the first in Europe, School of Hygiene. Additionally, due to the typhus epidemic, the fundaments for the State Sanitary Inspection (1954), which is functioning until this day, were laid down along with various sanitary acts.